Cold pools over the Netherlands: A statistical study from tower and radar observations. (27th December 2021) - Kruse, Irene L.; Haerter, Jan O.; Meyer, Bettina
Abstract: We provide a detailed analysis of convectively generated cold pools (CPs) over flat midlatitude land, combining ten‐year high‐frequency time series of measurements at several heights available from the 213‐m tower observatory at Cabauw, the Netherlands, with a collocated 2D radar rainfall dataset. This combination of data allows us to relate observations of the CP's temporal and vertical structure to the properties of each CP's parent rain cell, which we identify by rain‐cell tracking. Using a new detection method, based on the anomalies of both the vertically averaged wind and the temperature, we monitor the arrival and passing of 189 CPs during ten summers (2010–2019). The time series show a clear signature of vortex‐like motion along the leading CP edge in the vertical and horizontal wind measurements. The arrival of CP gust fronts is characterized by a steep decrease in both temperature and moisture, with a recovery time of approximately two hours. We see no evidence of moisture rings on the gust front edge, and therefore no indications for thermodynamic convective triggering. From the tower data, we obtain a median CP temperature drop of T drop ≈ − 2 . 9   K and a height‐averaged horizontal wind anomaly of Δ u max ≈  4.4 m · s − 1 . Relating the individual CP's horizontal wind anomalies and temperature drops, we confirm the validity of the theoretical density current relationship, Δ u max ∝ T drop 1 / 2 . We further propose a simple statistical model to relate the CP strength defined by T drop to the environmental properties influencing the CP: rain intensity and lower boundary‐layer saturation. A multivariate linear regression suggests a 1   K colder CP for a 4 mm · hr − 1 more intense rain cell (instantaneous area‐averaged rain intensity) or for a 2 . 5   K larger pre‐CP dew‐point depression. Abstract : A convectively generated cold pool (CP) is a subcloud volume of air, cooled by the partial evaporation of precipitation, which descends and spreads out as a density current when hitting the surface. This study presents a thorough statistical analysis of observed CP properties over midlatitude coastal land. The combination of data from radar reflectivities and a 213‐m boundary‐layer measurement tower located in the Netherlands allows us to relate vertical observations of lower CP structure to the properties of the parent rain cell.